Precipitation and Lake Water Evaporation Recorded by Terrestrial and Aquatic n‐Alkane δ2H Isotopes in Lake Khar Nuur, Mongolia. (17th February 2022) - Strobel, Paul; Struck, Julian; Bazarradnaa, Enkhtuya; Zech, Michael; Zech, Roland; Bliedtner, Marcel
Abstract: The compound‐specific hydrogen isotopic composition (δ 2 H) of n ‐alkanes is a valuable proxy to investigate hydrological conditions in lake sediments. While terrestrial n ‐alkanes reflect the isotopic signal of the local precipitation, aquatic n ‐alkanes incorporate the isotopic signal of the lake's water, which can be strongly modulated by evaporative enrichment. So far, the spatial distribution of the terrestrial and aquatic δ 2 H signal within lakes have not systematically been investigated. Here, we present compound‐specific δ 2 H results of terrestrial (δ 2 HC31 ) and aquatic (δ 2 HC23 ) n ‐alkanes of surface sediment samples from Lake Khar Nuur, a semi‐arid and high‐altitude lake in the Mongolian Altai, and additionally investigate the δ 2 H signal of topsoils from the catchment. Our results show that the majority of the n ‐alkane δ 2 H values from the catchment topsoils correspond well with modeled local growing season precipitation (JJAS). However, few samples in the northern catchment show more positive δ 2 H values possibly due to increased evapo(transpi)ration by southward exposition and shallower soils there. The only small variability of δ 2 HC31 in the surface sediments is in the range of most topsoils δ 2 H from the catchment, and thus, well reflects local growing season precipitation. δ 2 HC23 in surface sediment samples from the central and deepest parts of the lake, that is, the lake's sediment accumulation zones, shows distinctly more positive δ 2 HC23 values due to evaporative lake water enrichment. Consequently, Δaq‐terr, which is the isotopic offset between δ 2 HC23 and δ 2 HC31, indicates distinct lake water enrichment in the lake's accumulation zones and is a valuable proxy to investigate past hydrological changes. Key Points: The hydrogen isotopic composition of terrestrial C31 n ‐alkanes reflects the local growing season precipitation at Lake Khar Nuur Aquatic C23 n ‐alkanes incorporate the isotopic signal of the lake's water, which is strongly modulated by evaporative enrichment The isotopic offset between C23 and C31 is a valuable proxy for evaporation in the lake and past hydrological changes in the catchment